Membangun Karakter Konservasi melalui Origami bagi Pembelajar Bahasa Jepang - Lispridona Diner (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Character education has an important role in individual development. Every individual who has good character starts early. In Indonesia, character education in recent years has become part of formal education. It starts with character-based PAUD, followed by SD to SMA/MK/MAN which uses a curriculum known as the 2013 curriculum (kurtilas or K13). At universities such as Semarang State University (UNNES) since March 12, 2010 Unnes declared itself to be a Conservation University. As a Conservation University, since then UNNES has a vision of